A mineralizing solution, a photoresponsive biomimetic mineralized dentin micro / nano structure, and its preparation method

The mineralization solution formed by mixing carboxylated gold nanoparticles with calcium and phosphorus sources achieves the remineralization and antibacterial functionalization of demineralized dentin, solving the problems of low mechanical strength and poor antibacterial properties of dentin in existing technologies, restoring the structure and function of dentin, and is suitable for tooth defect repair.

CN120713766BActive Publication Date: 2025-11-14WUHAN UNIV OF TECH
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202511220195.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-08-29
Publication Date
2025-11-14
Estimated Expiration
2045-08-29

AI Technical Summary

Technical Problem

Existing biomimetic mineralized dentin has low mechanical strength and poor antibacterial properties, making it difficult to effectively protect the structural integrity and antibacterial activity of teeth in complex oral environments.

Method used

A mineralization solution was formed by mixing carboxylated gold nanoparticles with calcium and phosphorus sources. A photoresponsive biomimetic mineralization method was used to form a photoresponsive biomimetic dentin micro-nano structure on demineralized dentin sheets. The HAP crystals in demineralized dentin collagen were formed by utilizing the chelation between carboxylated gold nanoparticles and mineral ions. The crystals generated thermal stimulation and reactive oxygen species under near-infrared light irradiation.

Benefits of technology

It restores the hierarchical structure and mechanical properties of dentin, possesses excellent biocompatibility and antibacterial activity, and can enhance its antibacterial effect under near-infrared light irradiation, making it suitable for the field of tooth defect restoration.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120713766B_ABST
    Figure CN120713766B_ABST
Patent Text Reader

Abstract

This invention relates to a mineralizing solution, a photoresponsive biomimetic mineralized dentin micro / nanostructure, and its preparation method. The mineralizing solution comprises 100–1000 μg / mL of carboxylated gold nanoparticles, 4.0–5.0 mmol / L of calcium source, and 1.5–2.5 mmol / L of phosphorus source. Demineralized dentin sheets are placed in the above mineralizing solution for biomimetic mineralization, forming a photoresponsive biomimetic mineralized dentin composite micro / nanostructure. This invention uses carboxylated gold nanoparticles with calcium and phosphorus sources to form a calcium phosphate mineralizing solution containing gold nanoparticles, which can achieve complete remineralization of demineralized dentin. By controlling the concentration of carboxylated gold nanoparticles, the mineralization effect is ensured, achieving the formation of HAP crystals within the demineralized dentin collagen, restoring the dentin hierarchical structure, and restoring the mechanical properties of dentin to a level comparable to natural dentin. Simultaneously, it can synergistically generate thermal stimulation and reactive oxygen species under NIR light irradiation, exhibiting excellent biocompatibility and antibacterial activity under near-infrared light stimulation.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of dentin restoration technology, specifically relating to a mineralizing solution, a photoresponsive biomimetic mineralized dentin micro / nano structure, and its preparation method. Background Technology

[0002] Dentin is a hierarchically ordered organic-inorganic composite biomaterial with mineralized collagen as its basic building block. Its excellent mechanical strength and fatigue resistance stem from the microstructure of hydroxyapatite (HAP) deposited along the long axis within collagen fibers. Generally, dentin is in a dynamic equilibrium between demineralization and remineralization, exhibiting good structural integrity and biological stability, effectively protecting the internal dental pulp tissue from mechanical stress, bacteria, and other external stimuli.

[0003] However, due to the complex and dynamic oral environment in which teeth exist, excessive sugar intake, consumption of carbonated beverages, and poor oral hygiene habits can all lead to bacterial colonization and proliferation on the tooth surface, forming a biofilm. Bacterial acid production within the biofilm induces dentin demineralization, and the dissolution of HAP (hydrogen peroxide) within collagen fibers further collapses the unsupported dentin-collagen network, severely affecting the penetration of bonding materials. The gaps at the bonding site then become a breeding ground for moisture, hydrolytic enzymes, and bacteria, leading to secondary caries and significantly reducing the long-term durability of restorative treatments. Simultaneously, demineralized dentin, as a weak layer in the tooth structure, can also become an early window for dentin hypersensitivity, pulpitis, and even periapical periodontitis. Ideal dentin restoration treatment should simultaneously restore the integrity of the dentin structure and its antibacterial activity.

[0004] In recent years, with the emergence of the concept of biomimetic mineralization, intrafiber mineralization has become an effective strategy to reverse dentin demineralization. This involves adding polymers such as polyaspartic acid (PASP), polyacrylic acid (PAA), and polyacrylamide hydrochloride (PAH) to the mineralization solution to form a polymer-induced liquid phase precursor (PILP). The PILP can then crystallize and transform within the dentin collagen fibers, thereby restoring the natural hierarchical structure of dentin. However, due to the low elastic modulus and strength of polymers and their poor biological activity, biomimetic mineralized dentin induced by existing mineralization precursors still suffers from poor mechanical strength and difficulty resisting the bacterial environment of the oral cavity. Therefore, there is an urgent need to develop a novel mineralization precursor to construct a biomimetic mineralized dentin micro / nano composite structure that combines excellent mechanical properties and antibacterial characteristics, thereby improving the long-term effectiveness of clinical restorative treatments. Summary of the Invention

[0005] The purpose of this invention is to overcome the above-mentioned technical deficiencies and provide a mineralizing liquid, a photoresponsive biomimetic mineralized dentin micro / nano structure and its preparation method, thereby solving the technical problems of low mechanical strength and poor antibacterial properties of the biomimetic mineralized dentin induced in the prior art.

[0006] To achieve the above-mentioned technical objectives, the technical solution provided by this invention is as follows:

[0007] In a first aspect, the present invention provides a mineralization solution comprising 100–1000 μg / mL of carboxylated gold nanoparticles, 4.0–5.0 mmol / L of calcium source, and 1.5–2.5 mmol / L of phosphorus source.

[0008] Secondly, the present invention provides a method for preparing a mineralizing solution, comprising the following steps: adding carboxylated gold nanoparticles to a phosphorus source solution, dispersing them uniformly by ultrasonication, adding a calcium source and mixing them uniformly to obtain a mineralizing solution.

[0009] Thirdly, the present invention provides a method for preparing a photoresponsive biomimetic mineralized dentin micro / nano structure, comprising the following steps: placing a demineralized dentin sheet in the above-mentioned mineralization solution to perform biomimetic mineralization, thereby forming a photoresponsive biomimetic mineralized dentin composite micro / nano structure.

[0010] Fourthly, the present invention provides a photoresponsive biomimetic mineralized dentin micro / nano structure prepared by the above-described preparation method.

[0011] Compared with the prior art, the beneficial effects of the present invention include:

[0012] This invention utilizes carboxylated gold nanoparticles (AuNPs-COOH) with calcium and phosphorus sources to form a calcium phosphate mineralization solution containing gold nanoparticles. This solution can achieve complete remineralization of demineralized dentin, and the mineralization effect is ensured by controlling the concentration of carboxylated gold nanoparticles. When demineralized dentin sheets are placed in this mineralization solution, on the one hand, a mineralization precursor is formed through the chelation between AuNPs-COOH and mineral ions. Following biomimetic mineralization, HAP crystals are formed within the demineralized dentin collagen, restoring the dentin hierarchical structure. On the other hand, after mineralization, AuNPs-COOH is doped into the biomimetic mineral... In the dentin micro-nano structure, not only are the mechanical properties of dentin restored to be comparable to those of natural dentin, but it also possesses certain antibacterial properties. At the same time, it can synergistically generate thermal stimulation and reactive oxygen species under near-infrared (NIR) light irradiation. Therefore, the photoresponsive biomimetic mineralized dentin micro-nano structure of this invention has photothermal and photodynamic effects in response to near-infrared light. It can exhibit excellent biocompatibility and antibacterial activity under near-infrared light stimulation, realizing the transformation of dentin repair from structural biomimetic to structure-function dual biomimetic. At the same time, it provides a new direction for the precise prevention and control of secondary caries through composite stimulus-responsive materials, which is especially suitable for the field of tooth defect repair. Attached Figure Description

[0013] Figure 1The images shown are SEM images and EDS spectra of the demineralized dentin (DMD) prepared in Comparative Example 2 of this invention. In the images, a1 and a2 are longitudinal cross-sectional views of the DMD, and a2 is an enlarged view of a1; b1 and b2 are cross-sectional views of the DMD, and b2 is an enlarged view of b1; c1-c3 are distribution maps of calcium, phosphorus, and gold elements, respectively; and c4 is an elemental energy spectrum.

[0014] Figure 2 The images shown are SEM images and EDS spectra of the PAA-ACP biomimetic mineralized dentin sheet (PRD) prepared in Comparative Example 3 of this invention. In the images, a1 and a2 are longitudinal cross-sectional views of the PRD, and a2 is an enlarged view of a1; b1 and b2 are cross-sectional views of the PRD, and b2 is an enlarged view of b1; c1-c3 are distribution maps of calcium, phosphorus, and gold elements, respectively; and c4 is an elemental energy spectrum.

[0015] Figure 3 The images shown are SEM images and EDS spectra of the photoresponsive biomimetic mineralized dentin micro / nanostructure (ARD) prepared in Example 1 of this invention. In the images, a1 and a2 are longitudinal cross-sectional views of the ARD, and a2 is an enlarged view of a1; b1 and b2 are cross-sectional views of the ARD, and b2 is an enlarged view of b1; c1-c3 are distribution maps of calcium, phosphorus, and gold elements, respectively; and c4 is the elemental energy spectrum.

[0016] Figure 4 The XRD pattern of this invention;

[0017] Figure 5 The results of the nanoindentation test of this invention;

[0018] Figure 6 The results of the photothermal performance test of the present invention are shown, where a represents the photothermal curves of Comparative Example 3 and Example 1 under NIR illumination of different powers, and b represents 1.5 W / cm². 2 Photothermal imaging images of Comparative Example 3 and Example 1 under NIR illumination at 1.5 W / cm². c represents Example 1 under NIR illumination at 1.5 W / cm². 2 Heating curves under NIR illumination and cooling curves after illumination is turned off, where d represents Example 1 at 1.5 W / cm². 2 Five thermal cycling curves under NIR illumination at high power;

[0019] Figure 7 The results of the photodynamic performance test of the present invention are shown, where a is the TMB reactive oxygen species test result of Example 1, and b is the singlet oxygen species test result of Example 1. 1 The EPR spectrum of O2), c is the superoxide anion (·O2) from Example 1. - The EPR spectrum of the NIR spectrum was obtained with an applied NIR power of 1.5 W / cm². 2 The time is 15 minutes;

[0020] Figure 8The quantitative antibacterial detection results of this invention are shown, where a represents the results of Comparative Example 2 (DMD), Comparative Example 3 (PRD), and Example 1 (ARD). S. mutans Colony optical photograph, b is S. mutans CFU count of colonies, c is crystal violet staining OD 595nm Absorbance value;

[0021] Figure 9 For the present invention's resistance S. mutans The results of staining live / dead bacteria in the biofilm, where a1-c1 represent the staining of Comparative Example 2 (DMD), Comparative Example 3 (PRD), and Example 1 (ARD) under conditions without NIR illumination. S. mutans Representative CLSM three-dimensional images of biofilms, a2-c2 are Comparative Example 2 (DMD), Comparative Example 3 (PRD), and Example 1 (ARD) under conditions without NIR illumination. S. mutans Distribution curves of live / dead bacteria in different layers of the biofilm; d1-f1 represent the distribution at 1.5 W / cm². 2 Comparative Example 2 (DMD), Comparative Example 3 (PRD), and Example 1 (ARD) under NIR illumination of varying power S. mutans Representative CLSM three-dimensional images of biofilms, d2-f2 at 1.5 W / cm² 2 Comparative Example 2 (DMD), Comparative Example 3 (PRD), and Example 1 (ARD) under NIR illumination of varying power S. mutans Distribution curves of live / dead bacteria in different layers of a biofilm;

[0022] Figure 10 For the present invention's resistance S. mutans Representative SEM images of the biofilm, where a1-c1 are Comparative Example 2 (DMD), Comparative Example 3 (PRD), and Example 1 (ARD) under conditions without NIR illumination. S. mutans Low-magnification SEM images of the biofilm, a2-c2 are Comparative Example 2 (DMD), Comparative Example 3 (PRD), and Example 1 (ARD) under conditions without NIR illumination. S. mutans High-magnification SEM image of the biofilm, d1-f1 at 1.5 W / cm². 2 Comparative Example 2 (DMD), Comparative Example 3 (PRD), and Example 1 (ARD) under NIR illumination of varying power S. mutans Low-magnification SEM image of biofilm, d2-f2 at 1.5 W / cm². 2 Comparative Example 2 (DMD), Comparative Example 3 (PRD), and Example 1 (ARD) under NIR illumination of varying power S. mutans High-magnification SEM image of biofilm, circled areas represent S. mutans The shape changes are represented by the boxed area. S. mutans Structural rupture;

[0023] Figure 11 The in vivo antibacterial performance test results of the present invention are shown in the following: a is an optical photograph of bacterial colonies isolated from the surface of a dentin slice sample after 14 days of culture in the oral cavity of a rat; b is the corresponding quantitative count of CFU; and c is the corresponding representative SEM image.

[0024] Figure 12 The in vivo biocompatibility test results of this invention are shown in the HE staining images of important organs (heart, lung, spleen, liver, and kidney) with a scale bar of 1 mm.

[0025] Figure 13 The images shown are SEM images of the photoresponsive biomimetic mineralized dentin micro / nano structures prepared in Example 2 of this invention. In the images, a1 is a low-magnification image of the longitudinal section, a2 is a high-magnification image of the longitudinal section, b1 is a low-magnification image of the cross section, and b2 is a high-magnification image of the cross section. Detailed Implementation

[0026] To make the objectives, technical solutions, and advantages of this invention clearer, the invention will be further described in detail below with reference to the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are merely illustrative and not intended to limit the invention.

[0027] To address the shortcomings of existing biomimetic mineralized dentin, such as low mechanical strength and poor antibacterial properties, this invention provides a mineralizing solution, a photoresponsive biomimetic mineralized dentin micro / nano structure, and a preparation method that simultaneously achieves remineralization of demineralized dentin collagen network and antibacterial functionalization.

[0028] In a first aspect, the present invention provides a mineralization solution comprising 100–1000 μg / mL of carboxylated gold nanoparticles, 4.0–5.0 mmol / L of calcium source, and 1.5–2.5 mmol / L of phosphorus source.

[0029] This invention mixes carboxylated gold nanoparticles (AuNPs-COOH) with calcium phosphate solution to obtain a calcium phosphate (Au-ACP) mineralization solution containing ultra-small gold nanoparticles. This solution can achieve complete remineralization of demineralized dentin, and the mineralization effect is ensured by controlling the concentration of carboxylated gold nanoparticles. If the concentration of AuNPs-COOH is below 100 μg / mL or above 1000 μg / mL, the demineralized dentin can only achieve partial remineralization or a very low degree of mineralization.

[0030] Specifically, the concentrations of carboxylated gold nanoparticles include, but are not limited to, 100 μg / mL, 120 μg / mL, 150 μg / mL, 180 μg / mL, 200 μg / mL, 220 μg / mL, 250 μg / mL, 280 μg / mL, 300 μg / mL, 350 μg / mL, 400 μg / mL, 450 μg / mL, 500 μg / mL, 550 μg / mL, 600 μg / mL, 650 μg / mL, 700 μg / mL, and 800 μg / mL. The concentrations of calcium sources include, but are not limited to, 4.0 mmol / L, 4.2 mmol / L, 4.4 mmol / L, 4.5 mmol / L, 4.6 mmol / L, 4.8 mmol / L, and 5.0 mmol / L; the concentrations of phosphorus sources include, but are not limited to, 1.5 mmol / L, 1.6 mmol / L, 1.8 mmol / L, 2.0 mmol / L, 2.2 mmol / L, and 2.5 mmol / L.

[0031] Preferably, the carboxylated gold nanoparticles are prepared by reducing chloroauric acid and mercaptopropionic acid with sodium borohydride.

[0032] The sodium borohydride reduction method proposed in this invention is an existing method for preparing gold nanoparticles. For details, refer to the preparation steps of AuNPs3 in the literature Size-Effect of Gold Nanoparticles and Nanoclusters to Inhibit Amyloid-βFibrillation (DOI:10.1039 / c7nr00699c), only the ligand GSH is replaced with mercaptopropionic acid.

[0033] In this invention, mercaptopropionic acid is used as a ligand to prepare carboxylated gold nanoparticles. The chelation between carboxylated gold nanoparticles and mineral ions can induce the formation of mineralization precursors and HAP crystals in demineralized dentin collagen, restore the dentin hierarchical structure, and improve the mechanical properties of dentin. Furthermore, the carboxylated gold nanoparticles are incorporated into remineralized dentin collagen, giving the remineralized dentin a certain degree of antibacterial activity. At the same time, they can synergistically generate thermal stimulation and reactive oxygen species under NIR light irradiation, further enhancing the antibacterial effect.

[0034] Preferably, the particle size of the carboxylated gold nanoparticles is 3–6 nanometers. In this invention, if the particle size of the carboxylated gold nanoparticles is too small, the preparation conditions are harsh and the cost is high; if the particle size is too large, it is not conducive to the remineralization effect.

[0035] Preferably, the solvent of the mineralizing solution is a tris(hydroxymethyl)aminomethane (Tris) buffer solution containing 9–11 mmol / L Tris and 135–150 mmol / L sodium chloride, with a pH of 7.2–7.6.

[0036] Preferably, the calcium source includes calcium chloride dihydrate, and the phosphorus source includes disodium hydrogen phosphate dodecahydrate.

[0037] Secondly, the present invention provides a method for preparing a mineralizing solution, comprising the following steps: adding carboxylated gold nanoparticles to a phosphorus source solution, dispersing them uniformly by ultrasonication, adding a calcium source and mixing them uniformly to obtain a mineralizing solution.

[0038] Thirdly, the present invention provides a method for preparing a photoresponsive biomimetic mineralized dentin micro / nano structure, comprising the following steps: placing a demineralized dentin sheet in the above-mentioned mineralization solution to perform biomimetic mineralization, thereby forming a photoresponsive biomimetic mineralized dentin composite micro / nano structure.

[0039] The photoresponsive biomimetic mineralized dentin composite micro / nano structure of this invention is composed of AuNPs-COOH and HAP as minerals, and has NIR-responsive photothermal and photodynamic effects. It can exhibit excellent biocompatibility and antibacterial activity under NIR light stimulation.

[0040] Preferably, the wavelength of NIR light stimulation is 808 nanometers, and the stimulation time is 10 to 15 minutes.

[0041] Preferably, the demineralized dentin sheet is prepared by etching the dentin sheet with 37wt% phosphoric acid etching agent for 20-40 seconds.

[0042] Preferably, biomimetic mineralization involves incubation at 35–38°C for 3–10 days, with the solution changed every 2–4 days. Specifically, the biomimetic mineralization temperature includes, but is not limited to, 35°C, 36°C, 37°C, and 38°C; the incubation time includes, but is not limited to, 3 days, 4 days, 5 days, 5.5 days, 6 days, 7 days, 8 days, 9 days, and 10 days; and the solution change interval includes, but is not limited to, 2 days, 3 days, and 4 days.

[0043] Fourthly, the present invention provides a photoresponsive biomimetic mineralized dentin micro / nano structure prepared by the above-described preparation method.

[0044] Fifthly, the present invention provides an application of the above-mentioned photoresponsive biomimetic mineralized dentin micro / nano structure in the preparation of dental restorative treatment and secondary caries prevention materials.

[0045] The photoresponsive biomimetic mineralized dentin micro / nanostructure provided by this invention is a remineralized dentin micro / nanostructure composed of AuNPs-COOH nanoparticles. On the one hand, it forms a mineralization precursor through the chelation between AuNPs-COOH and mineral ions, and achieves the formation of HAP crystals in demineralized dentin collagen through a biomimetic mineralization process, restoring the dentin hierarchical structure. On the other hand, after mineralization, AuNPs-COOH is doped into the biomimetic mineralized dentin micro / nanostructure, which not only restores the mechanical properties of dentin to a level comparable to natural dentin, but also can synergistically generate thermal stimulation and reactive oxygen species under NIR light irradiation, exhibiting excellent antibacterial activity.

[0046] This invention presents a photoresponsive biomimetic mineralized dentin micro / nano structure, which realizes the transformation of dentin repair from structural biomimicry to structure-function dual biomimicry. At the same time, it provides a new direction for the precise prevention and control of secondary caries through composite stimulus-responsive materials. This is of great significance for improving tooth defect repair technology and optimizing treatment results.

[0047] The present invention will be further described in detail below through specific embodiments. Unless otherwise specified, all raw materials, reagents, instruments, and equipment used in the present invention can be obtained by purchasing them from the market or by existing methods. The dentin sheet is obtained as follows: After approval by the ethics committee, caries-free third molars are collected, surface tissues and contaminants are removed, and the sheets are stored in a 0.5% thymol solution at 4°C for use within one month. The sheets are cut parallel to the crown using a diamond saw blade under low-speed water cooling to obtain dentin sheets with a thickness of approximately 1 mm. Subsequently, the surface of the dentin sheet is wet-polished with 800, 1200, and 2400 grit silicon carbide sandpaper. After ultrasonic removal of impurities remaining after polishing, the dentin sheet (SD) is stored in deionized water at 4°C for use within 24 hours. AuNPs-COOH nanoparticles are prepared according to the preparation steps of AuNPs3 in the literature DOI:10.1039 / c7nr00699c, except that the ligand GSH is replaced with mercaptopropionic acid.

[0048] Example 1

[0049] A method for fabricating a photoresponsive biomimetic mineralized dentin micro / nano structure includes the following steps:

[0050] (1) Preparation of Au-ACP mineralization solution: Using Tris buffer solution (containing 10 mM Tris and 150 mM sodium chloride, pH = 7.4) as solvent, and calcium chloride dihydrate and disodium hydrogen phosphate dodecahydrate as calcium and phosphorus sources, respectively, 50 mL of 9 mM calcium solution and 50 mL of 4.2 mM phosphate solution were prepared. 0.025 g AuNPs-COOH nanoparticles were added to 50 mL of 4.2 mM phosphate solution, dispersed by sonication for 10 minutes, and then mixed with an equal volume of 9 mM calcium solution to obtain 250 μg / mL Au-ACP mineralization solution.

[0051] (2) Preparation of demineralized dentin sheets: 37wt% phosphoric acid etchant was applied to the surface of the dentin sheet, etched for 30 seconds, and then rinsed with deionized water for 1 minute to remove the phosphoric acid etchant, thus obtaining the demineralized dentin sheet, which was stored at 4℃ for later use.

[0052] (3) Preparation of photoresponsive biomimetic mineralized dentin micro-nano structure: Demineralized dentin sheets were immersed in the above 250 μg / mL Au-ACP mineralization solution, incubated at 37℃ for 7 days, the solution was changed every 3 days, and the photoresponsive biomimetic mineralized dentin micro-nano structure (ARD) was obtained after natural drying.

[0053] Example 2

[0054] The only difference from Example 1 is that the concentration of Au-ACP mineralization solution is 1000 μg / mL, while the other steps and conditions are the same as in Example 1.

[0055] Comparative Example 1

[0056] Normal dentin film (SD) (not etched with 37wt% phosphoric acid etching agent).

[0057] Comparative Example 2 (Preparation of Demineralized Dentin Tablets DMD)

[0058] The difference from Example 1 is that the demineralized dentin slices were incubated in a Tris buffer solution instead of an Au-ACP mineralizing solution, while the other steps and conditions were the same as in Example 1.

[0059] Comparative Example 3 (Preparation of PAA-ACP biomimetic mineralized dentin sheet PRD)

[0060] The difference from Example 1 is that the demineralized dentin sheet was incubated in a PAA-ACP mineralization solution containing 25 μg / mL polyacrylic acid (PAA) instead of 250 μg / mL AuNPs-COOH.

[0061] Performance testing

[0062] (1) Morphological composition characterization of photoresponsive biomimetic mineralized dentin micro / nanostructure

[0063] Dentin slices were fixed with glutaraldehyde, dehydrated using a gradient of ethanol, replaced with hexamethyldisilazane, and vacuum dried before morphological and compositional analysis using scanning electron microscopy (SEM). The results showed that, in Comparative Example 2, the demineralized dentin (DMD) surface had exposed collagen fibers, such as... Figure 1 As shown in a1-a2 and b1-b2, even the typical collagen fiber D-band structure can be observed. Figure 1 (a2). Due to the loss of mineral support, the collagen network visibly collapses, and some collagen fibers break down. (e.g., ...) Figure 1 As shown in c1-c4, the EDS elemental energy spectrum only detected C element, and there was no signal of Ca or P element, indicating that the dentin sheet underwent mineralization and demineralization.

[0064] Comparative Example 3: Dentin PRD after PAA-ACP biomimetic mineralization Figure 2 As shown, in Example 1, the dentin ARD treated with Au-ACP biomimetic mineralization is as follows: Figure 3 As shown, all of them restored their original continuous three-dimensional network structure, with collagen fibers fully filled and the surface displaying a rough needle-like HAP crystal morphology. Figure 2 a1-a2 and b1-b2, Figure 3 (a1-a2 and b1-b2). Furthermore, the EDS spectrum shows that Ca and P elements are uniformly distributed on the surface of the dentin section, exhibiting significant signals of Ca, P, and O elements in the spectrum. Figure 2 c1-c4, Figure 3 In particular, in Example 1, Au was observed to be uniformly distributed on the dentin surface (c1-c4). Figure 3 (c3) confirmed that AuNPs-COOH nanoparticles were successfully composited in a biomimetic mineralized dentin micro / nano structure.

[0065] (2) Phase characterization of photoresponsive biomimetic mineralized dentin micro / nanostructures

[0066] Dentin slices were freeze-dried and then analyzed for phase composition by X-ray diffraction (XRD). Results are as follows: Figure 4 As shown, after demineralization, the diffraction peaks at 2θ = 26° and 2θ = 32° in Comparative Example 2 (DMD) were significantly reduced, corresponding to the HAP (002) and (211) crystal planes, indicating that the HAPs within the dentin collagen network were sufficiently etched. Comparative Example 3 (PRD) and Example 1 (ARD) showed obvious diffraction peaks at 2θ = 26° and 2θ = 32°, consistent with the healthy dentin (SD) in Comparative Example 1, indicating successful induction of dentin collagen fiber remineralization, and the resulting mineral crystals being identical to natural dentin.

[0067] (3) Characterization of the mechanical properties of photoresponsive biomimetic mineralized dentin micro / nanostructures

[0068] The mechanical properties of the dentin slices were tested using a nanoindentation analyzer (Hysitron TI 980, Bruker, German). The results are as follows: Figure 5 As shown, the elastic modulus and hardness of Example 1 (ARD) are 24.42 GPa and 1.058 GPa, respectively, which are close to the results of Comparative Example 1 (SD) (elastic modulus and hardness are 24.84 GPa and 1.15 GPa, respectively). In contrast, the elastic modulus and hardness of Comparative Example 2 (DMD) are 6.37 GPa and 0.175 GPa, respectively, and those of Comparative Example 3 (PRD) are 15.29 GPa and 0.44 GPa, respectively. Therefore, the photoresponsive biomimetic mineralized dentin micro / nanostructure ARD of this invention not only restores the hierarchical structure of demineralized dentin but also achieves mechanical properties comparable to natural dentin.

[0069] (4) Detection of the photoresponse performance of photoresponsive biomimetic mineralized dentin micro / nanostructures

[0070] (4-1) Performance testing of photothermal therapy (PTT) of light-responsive biomimetic mineralized dentin micro / nanostructures

[0071] To evaluate the PTT performance of Example 1 (ARD) and Comparative Example 3 (PRD), an 808 nm NIR laser emitter was used as the light source, and a Uti-320E infrared thermal imager was used to monitor the temperature changes of dentin sections. The thermal stability of ARD was evaluated through five consecutive heating-cooling cycles. The results showed that ( Figure 6 In Example 1 (ARD), under NIR irradiation with power ranging from 0.5 to 1.5 W / cm², a significant temperature rise was observed, and the equilibrium temperature was reached within 3 minutes. Figure 6 As shown in (a) and (b) in the figure, when the power is increased sequentially from 0.5 W / cm² to 1 W / cm² and 1.5 W / cm², the equilibrium temperature rises from 28℃ to 36℃ and 47℃, respectively, and its PTT effect is not affected by the heating-cooling cycle. Comparative Example 3 (PRD), however, shows no significant temperature increase under NIR irradiation at all power levels. Figure 6 (As shown in (c) and (d)). This demonstrates that the photoresponsive biomimetic mineralized dentin micro / nanostructure (ARD) of this invention possesses excellent PTT performance and photothermal cycling stability.

[0072] (4-2) Performance testing of photodynamic therapy (PDT) using light-responsive biomimetic mineralized dentin micro / nanostructures

[0073] To evaluate the PDT performance of Example 1 (ARD), the 3,3',5,5'-tetramethylbenzidine (TMB) reactive oxygen species detection method and electron paramagnetic resonance spectroscopy (EPR, EMXplus, Bruker, German) were compared at 1.5 W / cm². 2 The total amount and species types of reactive oxygen species (ROS) generated in Example 1 (ARD) under 808 nm NIR irradiation were determined, with deionized water as the blank group.

[0074] The results show that ( Figure 7 The blank group (deionized water) did not show any obvious peaks, while AuNPs-COOH in Example 1 showed a characteristic peak of TMB oxidation at 652 nm without NIR excitation. Figure 7 As shown in (a), this is attributed to the inherent peroxidase-like activity of AuNPs-COOH. After NIR irradiation, the absorption peak at 652 nm increased significantly by more than 2 times, indicating that Example 1 (ARD) possesses PDT properties and can significantly promote ROS generation. Figure 7 The EPR spectra shown in (b) and (c) further confirm that the ROS formed by NIR excitation is singlet oxygen. 1 O2) and superoxide anion (·O2) - ).

[0075] (5) In vitro antibacterial performance testing of photoresponsive biomimetic mineralized dentin micro / nanostructure

[0076] To evaluate the in vitro antibacterial properties of Example 1 (ARD), Comparative Example 2 (DMD), and Comparative Example 3 (PRD), dentin slices were cut into identical sizes (0.6 × 0.6 × 1 cm). 3 After sterilization by ultraviolet light, it is subjected to anti-mutant streptococcus ( S. mutans Biofilm formation assay (UA159). Specific steps are as follows: Dilute with 39 mg / mL brain heart infusion broth (BHI) at a ratio of 1:100 and freeze. S. mutans The bacterial culture was prepared and amplified overnight at 37°C and 5% CO2. Subsequently, the bacterial culture was diluted to 10⁻¹⁰ with BHI medium containing 17 g / L sucrose. 5 CFU / mL concentration was added to well plates containing dentin samples. Two subgroups were set up: one without NIR light and the other with NIR light for 15 minutes. After treatment, the samples were incubated at 37°C for 24 hours to allow biofilm formation on the dentin sample surface. The biofilm inhibition effect was analyzed by plate counting (CFU method), crystal violet staining, live / dead bacteria staining, and SEM observation. The results are as follows: Figures 8-10 As shown.

[0077] The results showed that, compared with Comparative Example 2 (DMD) and Comparative Example 3 (PRD), the biofilm thickness and total bacterial count of Example 1 (ARD) were significantly reduced. Figure 8 In Example 1 (ARD), the CFU count decreased to 24.2% of that in Comparative Example 2 (DMD), and further decreased to 12.8% after NIR irradiation; crystal violet staining also showed consistent results. Live / dead bacterial staining results showed ( Figure 9 The biofilm thickness of Comparative Examples 2 (DMD) and 3 (PRD) reached 30 µm, mainly exhibiting strong green fluorescence, indicating a dense distribution of live bacteria within the biofilm. In contrast, the biofilm thickness of Example 1 (ARD) decreased to 10 µm, and red fluorescence significantly increased, indicating an increase in the content of dead bacteria in the biofilm. After applying NIR light irradiation, the biofilm volume and thickness of ARD Example 1 (ARD) further decreased, confirming that the photoresponsive biomimetic mineralized dentin micro / nanostructure can synergistically enhance antibacterial efficacy through PTT and PDT. SEM observation showed ( Figure 10 Regardless of the presence or absence of NIR light, the biofilms of Comparative Example 2 (DMD) and Comparative Example 3 (PRD) exhibited a continuous, dense, three-dimensional aggregated network, with elliptical Streptococcus mutans forming spatially heterogeneous microcolony structures through intercellular connections. Conversely, the total biofilm coverage of Example 1 (ARD) was significantly reduced, exhibiting a random island-like distribution, and the bacterial morphology transformed into a spherical shape (e.g., Figure 10 (as shown in the circular boxes (c2) and (f2)). Under NIR light irradiation, some bacteria exhibit cell wall wrinkling and localized perforation caused by photothermal heating (e.g. Figure 10 (as shown in the square box in f2). It can be seen that the photoresponsive biomimetic mineralized dentin micro / nano structure prepared by the present invention has excellent antibacterial activity, has the potential to restore the natural antibacterial activity of teeth and prevent secondary caries, and already has a significant antibacterial effect without near-infrared light stimulation, and the antibacterial effect is significantly enhanced after adding near-infrared light stimulation.

[0078] (6) Detection of in vivo antibacterial properties and biocompatibility of light-responsive biomimetic mineralized dentin micro / nanostructures

[0079] Animal experiments were conducted to further evaluate the in vivo antibacterial properties of the photoresponsive biomimetic mineralized dentin micro / nanostructure samples obtained in Example 1 (ARD), Comparative Example 2 (DMD), and Comparative Example 3 (PRD). With the approval of the Ethics Committee of Yanxuan Biotechnology (Hangzhou) Co., Ltd. (Experimental Animal License No.: SYXK2021-0043), approximately 3-week-old male Wistar rats (150 ± 10 g) were purchased from Spiford (Beijing) Biotechnology Co., Ltd., and randomly divided into 7 groups of 3 rats each.

[0080] Experimental groups (six groups in total): ARD, DMD, and PRD samples were cut into identical sizes (3 × 2 × 1 cm). 3 After being sterilized by ultraviolet light, the sample was fixed in the rat's oral cavity using a ligature wire. 200 μL of 1 × 10 8 CFU / mL standard S. mutans Bacterial suspension was applied to the sample surface and inoculated once daily for 7 consecutive days. Rats were fed a cariogenic diet containing high sugar and refined flour (Diet2000a) to simulate the oral pathogenic environment, ensuring adequate water supply. Each rat was fed twice daily, morning and evening, for a total of 15-20 grams per day until the end of the experiment. Two subgroups were established: one without NIR light irradiation and the other with 15 minutes of NIR light irradiation. The NIR light irradiation subgroup received vertical 808 nm NIR light irradiation at a power of 1.5 W / cm² for 15 minutes daily. Rats were prohibited from eating or drinking for 30 minutes after inoculation and treatment.

[0081] Control group (CON): No dentin sheets were fixed, and rats were fed only Diet2000a cariogenic diet under the same feeding conditions as the experimental group.

[0082] Seven days after the experiment, rats were euthanized using CO2 asphyxiation, and all dentin samples were collected. The in vivo antibacterial effect was evaluated using CFU and SEM. Major organs such as the heart, liver, spleen, lung, and kidneys of the rats were collected, fixed in 4% paraformaldehyde, embedded in paraffin, sectioned, and stained with hematoxylin and eosin (HE). In vivo biocompatibility was analyzed, and the results are as follows: Figures 11-12 As shown.

[0083] In vivo antibacterial results showed ( Figure 11 Compared with Comparative Example 2 (DMD) and Comparative Example 3 (PRD), Example 1 (ARD) S. mutans The number of bacteria was significantly reduced, especially after NIR light irradiation, with the bacterial count dropping to as low as 9% of that in Comparative Example 2 (DMD). Correspondingly, Figure 11 The SEM image shown in (c) shows that, due to the rinsing effect of saliva in the mouth, the bacteria on all dentin slices were relatively dispersed, and no obvious colonies were found. In fact, no bacteria were even observed in the two subgroups of Example 1 (ARD).

[0084] HE staining results showed that ( Figure 12There were no significant differences between Example 1 (ARD), Comparative Example 2 (DMD), and Comparative Example 3 (PRD) groups. No morphological or histological abnormalities were observed in the heart, spleen, lungs, and kidneys of any of the three groups. Only scattered lipid vacuoles (diameter <1 / 3 of a hepatocyte) were observed within the liver lobules, possibly related to mild fatty liver induced by the high-sugar Diet2000a cariogenic diet. Blood routine results showed no significant differences in red blood cells, white blood cells, and plasma proteins. Therefore, the in vivo antibacterial effect and biocompatibility of the photoresponsive biomimetic mineralized dentin micro / nanostructure of this invention were also verified.

[0085] (7) Morphological composition characterization of the photoresponsive biomimetic mineralized dentin micro / nanostructure obtained in Example 2

[0086] like Figure 13 As shown, after demineralized dentin was incubated at 37°C for 7 days in an Au-ACP mineralization solution containing 1000 μg / mL AuNPs-COOH, the dentin collagen network partially recovered its three-dimensional structure under crystal filling. Figure 13 (a1), and discontinuous crystal morphology was also observed within the collagen fibers ( Figure 13 (B1-B2), but some collagen remains in a collapsed state ( Figure 13 In Example a2), the Au-ACP-induced demineralization effect on dentin was reduced compared to Example 1. This demonstrates that a higher AuNPs-COOH concentration does not necessarily promote mineralization. In this invention, the concentration of carboxylated gold nanoparticles in the mineralization solution is preferably 100–1000 μg / mL, more preferably 100–500 μg / mL, and even more preferably 100–250 μg / mL.

[0087] In summary, the photoresponsive biomimetic mineralized dentin micro / nanostructures prepared in this invention can not only remineralize demineralized dentin, restoring its natural hierarchical structure and mechanical properties, but also synergize with the dual antibacterial mechanisms of PTT and PDT to effectively cope with the complex oral microenvironment, resist bacterial invasion, and further enhance the stability of the restored dentin. Furthermore, these micro / nanostructures possess good biocompatibility and are prepared under mild conditions with simple technology, making them highly suitable for the restorative treatment of dentin demineralization-related tooth defects.

[0088] The specific embodiments of the present invention described above do not constitute a limitation on the scope of protection of the present invention. Any other corresponding changes and modifications made in accordance with the technical concept of the present invention should be included within the scope of protection of the claims of the present invention.

Claims

1. A mineralizing solution, characterized in that, It includes carboxylated gold nanoparticles at a concentration of 100–500 μg / mL, a calcium source of 4.0–5.0 mmol / L, and a phosphorus source of 1.5–2.5 mmol / L; The carboxylated gold nanoparticles were prepared by reducing chloroauric acid and mercaptopropionic acid with sodium borohydride. The particle size of the carboxylated gold nanoparticles is 3-6 nm; The calcium source is calcium chloride dihydrate; the phosphorus source is disodium hydrogen phosphate dodecahydrate.

2. The mineralizing solution according to claim 1, characterized in that, The solvent of the mineralization solution is a tris(hydroxymethyl)aminomethane buffer solution containing 9–11 mmol / L tris(hydroxymethyl)aminomethane and 135–150 mmol / L sodium chloride, with a pH of 7.2–7.

6.

3. The method for preparing the mineralized solution according to any one of claims 1-2, characterized in that, The steps include: adding carboxylated gold nanoparticles to a phosphorus source solution, dispersing them evenly by ultrasonication, adding a calcium source and mixing evenly to obtain a mineralized solution.

4. A method for preparing a photoresponsive biomimetic mineralized dentin micro / nano structure, characterized in that, Includes the following steps: Demineralized dentin sheets are placed in the mineralization solution described in any one of claims 1-2 to perform biomimetic mineralization, forming a photoresponsive biomimetic mineralized dentin composite micro / nano structure.

5. The method for preparing the photoresponsive biomimetic mineralized dentin micro / nanostructure according to claim 4, characterized in that, The demineralized dentin sheet was prepared by etching the dentin sheet with 37wt% phosphoric acid etching agent for 20-40 seconds.

6. The method for preparing the photoresponsive biomimetic mineralized dentin micro / nanostructure according to claim 4, characterized in that, The biomimetic mineralization process involves incubating the organism in a 35–38°C incubator for 3–10 days, with the solution being changed every 2–4 days.

7. The photoresponsive biomimetic mineralized dentin micro / nanostructure prepared by the preparation method according to any one of claims 4-6.

Citation Information

Patent Citations

  • Method for quantitative detection of ultramicro-protein based on principle of biomineralization

    CN102230896A

  • PS (at) AuNPs composite microsphere as well as preparation and application thereof

    CN115608285A